Comparative study of electron density from incoherent scatter measurements at Arecibo with the IRI-95 model during solar maximum - N. K. Sethi; V. K. Pandey (Annales Geophysicae, 2000)
Arecibo (18.4 N, 66.7 W) incoherent scatter (IS) observations of electron density N(h) are compared with the International Reference Ionosphere (IRI-95) during midday (10–14 h), for summer, winter and equinox, at solar maximum (1981). The N(h) profiles below the F2 peak, are normalized to the peak density NmF2 of the F region and are then compared with the IRI-95 model using both the standard B0 (old option) and the Gulyaeva-B0 thickness (new option). The thickness parameter B0 is obtained from the observed electron density profiles and compared with those obtained from the IRI-95 using both the options. Our studies indicate that during summer and equinox, in general, the values of electron densities at all the heights given by the IRI model (new option), are generally larger than those obtained from IS measurements. However, during winter, the agreement between the IRI and the observed values is reasonably good in the bottom part of the F2 layer but IRI underestimates electron density at F1 layer heights. The IRI profiles obtained with the old option gives much better results than those generated with the new option. Compared to the observations, the IRI profiles are found to be much thicker using Gulyaeva-B0 option than using standard B0. Key words: Ionosphere (modelling and forecasting)